Who Establishes the Presence of a Mental Disorder in Defendants? Medicolegal Considerations on a European Court of Human Rights Case - Kooijmans, Tijs; Meynen, Gerben (Frontiers in Psychiatry, 2017)
Legal insanity is a peculiar element of criminal law, because it brings together two very different disciplines: psychiatry and psychology on the one hand, and the law on the other. One of the basic questions regarding evaluations of defendants concerns the question of who should establish ‘true mental disorder’, the judge or the behavioural expert? This question is complicated, and in this contribution it will be explored based on a Dutch case that was eventually decided by the European Court of Human Rights (ECtHR). We will argue that the ECtHR provides a valuable legal framework. Based on its merits, the framework could also be of interest to countries outside the Court’s jurisdiction.